Production of Medium-Chain-Length Poly(3-hydroxyalkanoates) from Crude Fatty Acids Mixture by Pseudomonas Putida - Annuar, M.S.M.; Tan, I.K.P.; Ibrahim, S.; Ramachandran, K.B. (2007)
Microbial production of medium-chain-length poly(3-hydroxyalkanoates), PHA(MCL) from crude fatty acids mixture was investigated. With ammonium as the growth limiting substrate, fatty acids mixture from saponified palm kernel oil (SPKO) supports good growth and PHA(MCL) production of Pseudomonas putida PGA1. Growth of this microorganism on ammonium exhibited substrate inhibition kinetics which can be described using Andrews model with the substrate inhibition constant, K = 1.2 g L-1. Concentration of SPKO in the aqueous medium should be at 10 g L-1 or less, as higher concentrations can significantly reduced the volumetric oxygen transfer coefficient (KA, biomass growth and PHA(MCL) production. Uptake of SPKO by the organism follows a zero-order kinetics, indicating a mass transfer limitation of the free fatty acids by the P putida PGA1 cells. In batch and fed-batch fermentations, PHA(MCL) accumulation is encouraged under ammonium-limited condition with SPKO as the sole carbon and energy source. The amount of PHAMCL accumulated and its specific production rate, PHA were influenced by the residual ammonium concentration level in the culture medium. It was observed that in both fermentation modes, when the residual ammonium becomes exhausted (<0.05 g L-1), the PHA(MCL) accumulation and q(PHA) were significantly reduced. However, this effect can be reversed by feeding low amount of ammonium to the culture, resulting in significantly improved PHA(MCL) yield and productivity. It is concluded that the feeding of residual ammonium concentration in the culture medium during the PHA(MCL) accumulation has a positive effect on sustaining the PHA(MCL) biosynthetic capability of the organism.